Proceedings IEEE COMPCON 97. Digest of Papers
DOI: 10.1109/cmpcon.1997.584710
|View full text |Cite
|
Sign up to set email alerts
|

A study of the cache and branch performance issues with running Java on current hardware platforms

Abstract: The Java bytecode language is emerging as a soft.-ware distribution standard. W i t h major vendors conimatted t o porting the Java run-time environment to their platforms, Java bytecode programs are expected to run without modification on multiple platforms. TFiese first generation run-time environmen,ts rely o n an, interpreter t o bridge the gap between the bytecode instructions and the native hardware. However, Java interpreters cause performance problems with, niicroarch,itectural features such as the cac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…The BTB target prediction accuracy is quite poor on object-oriented programs. Hsieh et al [1997] studied the performance of Java code running in interpreter mode and observed that microarchitectural mechanisms, such as BTB, are not well utilized. However, their work does not provide an in-depth characterization on Java indirect branches.…”
Section: Access Latency and Power Consumptionmentioning
confidence: 99%
“…The BTB target prediction accuracy is quite poor on object-oriented programs. Hsieh et al [1997] studied the performance of Java code running in interpreter mode and observed that microarchitectural mechanisms, such as BTB, are not well utilized. However, their work does not provide an in-depth characterization on Java indirect branches.…”
Section: Access Latency and Power Consumptionmentioning
confidence: 99%
“…Hsieh et al [15] compare the performance of the SUN JDK 1.0.2 Java interpreter, a bytecode to native code translator called Caffeine [16] and a compiled C/C++ version of the code. This is done based on simulations.…”
Section: Related Workmentioning
confidence: 99%
“…Romer et al [17] and Hsieh et al [8] evaluate the performance of Java programs, but their studies are limited to the interpreted Java programs and/or static executable images generated by a bytecode to native code translator. Radhakrishnan et al [15] compare the characteristics of both the JIT and the interpreter and their interaction with the architectural features such as the cache and branch prediction hardware.…”
Section: R E L a T E D W O R Kmentioning
confidence: 99%